The yeast actin-related protein Arp2p is required for the internalization step of endocytosis. - Moreau, V (1997)
The Saccharomyces cerevisiae actin-related protein Arp2p is an essential component of the actin cytoskeleton. We have tested its potential role in the endocytic and exocytic pathways by using a temperature-sensitive allele, arp2-1. The fate of the plasma membrane transporter uracil permease was followed to determine whether Arp2p plays a role in the endocytic pathway. Inhibition of normal endocytosis as revealed by maintenance of active uracil permease at the plasma membrane and strong protection against subsequent vacuolar degradation of the protein were observed in the mutant at the restrictive temperature. Furthermore, arp2-1 cells accumulated ubiquitin-permease conjugates, formed prior to internalization. These effects were also visible at permissive temperature, whereas the actin cytoskeleton appeared to be normally polarized. The soluble hydrolase carboxypeptidase Y and the lipophilic dye FM 4-64 were targeted normally to the vacuole in arp2-1 cells. Thus, Arp2p is required for internalization but does not play a major role in later steps of endocytosis. Synthetic lethality was demonstrated between arp2-1 and the endocytic mutant end3-1, suggesting participation of Arp2p and End3p in the same process. Finally, no evidence for a major defect in secretion was apparent; invertase secretion and delivery of uracil permease to the plasma membrane were unaffected in arp2-1 cells.